Peran Dinas Koperasi dan Usaha Mikro Dalam Memfasilitasi Akses Permodalan Bagi UMKM di Kabupaten Jember - Siti Rahmatillah N.S; Vita Dwi Lestari (Universitas 45 Surabaya, 2025)
The Field Experience Practice (PPL) is a compulsory course for students to gain real-world work experience before completing their studies. This research focuses on the role of the Cooperative and Micro Business Office of Jember Regency in facilitating access to capital for Micro, Small, and Medium Enterprises (MSMEs). The Cooperative Office plays a significant role in providing information, assistance, and facilitating access to capital through various programs and policies. This research uses a qualitative approach with interview and case study methods to evaluate the effectiveness of the implemented programs and MSME actors' perceptions of the office's performance.The results of the study show that the programs of the Cooperative and Micro Business Office of Jember Regency successfully increased access to capital, improved productivity, and supported the sustainability of MSME businesses. However, challenges remain in the delivery of information, the capital application process, and the relevance of training programs. Data from case studies show that 75% of registered MSMEs successfully obtained additional capital with an average income increase of 30%. The results of this research are expected to provide constructive input for improving the service quality of the Cooperative and Micro Business Office of Jember Regency.